Moderate and radical Islamic fundamentalism : the quest for modernity, legitimacy, and the Islamic state - Mawsilili, Ahmad (University Press of Florida, 1999)
Redefines the bases and scope of modern Islamic thought, suggesting that Islamic fundamentalism might prove to be a liberating theology for the modern Islamic world. Basing his argument largely on Arabic documents, Moussalli analyzes the basic concerns of fundamentalism--epistemology, knowledge, philosophy, modernity, and science as well as politics, political philosophy, and political economy. He examines the ideas of major Muslim thinkers who have affected the contemporary Islamic revival--especially Hasan al-Banna, Sayyid Qutb, and Hasan al-Turabi--showing the range of Islamic fundamentalist views from liberal democracy to authoritarianism. He then discusses how their thinking could affect an Islamic state, from political repression at one extreme to political representation at the other. From publisher description.